2015
DOI: 10.18632/oncotarget.5563
|View full text |Cite
|
Sign up to set email alerts
|

Dual mTORC1/C2 inhibitors: gerosuppressors with potential anti-aging effect

Abstract: Over the past decade, our understanding of the molecular and cellular mechanisms presiding over cellular and tissue decline with aging has greatly advanced. Classical hallmarks of aging cell include increasing levels of reactive oxygen species, DNA damage and senescence entry, which disrupt tissue architecture and function. Tissue dysfunction with aging has been shown to correlate with a cellular switch from a G0 reversible quiescence state into a G0 irreversible senescence state (geroconversion), causing a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Inactivation of the TORC1 pathway also causes cells to arrest in G1 (Sousa-Victor et al 2015), but cells neither increase in size during the arrest nor undergo senescence (Sousa-Victor et al 2015;Kucheryavenko et al 2019). RPE1-hTERT cells were arrested in G1 by treating them with 5 μM of the mTOR kinase inhibitor torin1, for 24 hours ( Figure 2F).…”
Section: Prolonged G1 Arrest Associated With Cell Size Increase Elicimentioning
confidence: 99%
“…Inactivation of the TORC1 pathway also causes cells to arrest in G1 (Sousa-Victor et al 2015), but cells neither increase in size during the arrest nor undergo senescence (Sousa-Victor et al 2015;Kucheryavenko et al 2019). RPE1-hTERT cells were arrested in G1 by treating them with 5 μM of the mTOR kinase inhibitor torin1, for 24 hours ( Figure 2F).…”
Section: Prolonged G1 Arrest Associated With Cell Size Increase Elicimentioning
confidence: 99%
“…When IPTG and rapamycin are washed out, cells re-proliferate [ 68 - 73 , 77 ]. Recently, we have shown that Torin 1 and PP242 suppresses geroconversion, prevent-ing senescent morphology and loss of RPP [ 78 , 79 ]. In agreement, reversal of senescent phenotype was shown by another pan-mTOR inhibitor, AZD8085 [ 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the PI3K/AKT/mTOR pathway independent of PTEN loss is also implicated in replicative senescence, and inhibition of mTOR was shown to prevent ageing in different experimental in vivo models [ 3 - 6 ]. Interestingly, rapamycin and metformin two potent mTOR inhibitors, suppress geroconversion, prevent cancer and have minor side effects when administered long-term in anti-aging doses [ 7 - 22 ]. Activation of the PI3K/AKT pathway is also implicated in UV induced cellular senescence, a phenomenon known as photo ageing.…”
Section: Introductionmentioning
confidence: 99%